PENGARUH TEKNIK ASSERTIVE TRAINING UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA MELALUI BIMBINGAN KELOMPOK DI SMP NEGERI 13 PEKANBARU - Wardhani, Regina Claudy; syahrilfuddin, syahrilfuddin; rosmawati, rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: This study aims to knowing the differences in self confidence of students before anda after assertivee training thehnique was applied through group guidance and knowing the effect of assertive training thechnique to improve student self confidence through group guidance. The study was conducted in pekanbaru state SMP 13 towards 7 subjects with purposive sampling technique. One group pre-test post-test model. The data collectionn instrumen used was a self confidence measurement. The results showed that there were differences in self confidence before and after being given assertive training technique with a significance value of 0,018 < 0,05. In addition, based on the spearman rank test, it is known that there is a significant effect between improve student’s self confidence significance 0,012< 0,05. The influence of assertive training technique to improve student self confidence is 75% ehole 25% effect by other factors that come from the student;s environtment. From the results obtained, it is recommended that educational institutions should continue to carry out activities that are able to improve student’s self confidence in the teaching and learning proccess to encourage more perpersonal communication in the teaching and learning proccess to encourage more positive thoughts, perceptions, insight and student attitudes. Key Words: Assertive training technique, self confidence, group guidance